Participatory Democracy and Political Parties of the New Left - Jarmara, Tomas (Civilia, 2012)
Paper is focused on theory of the participatory democracy and its connections with protest social movement and student's rebellions in the United States and Western Europe of the 60th years of the 20th Century, which stimulated the rise of the new political parties of the new left: environmental parties and left-wing libertarians parties.
Keywords: Participatory Democracy; Political Parties; New Left